(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2018)
The archaeological site of Guar Kepah lies in the state of Penang on the northern part of Peninsular Malaysia. Studies conducted in the area over a period of more than 155 years have revealed clear evidence of a coastal Neolithic community that adapted to its marine and estuarine environment. The fluctuation of sea levels and coastline changes affected ancient humans in Guar Kepah, as well as their subsistence pattern. A recent excavation in 2017 on a shell mound at site B has revealed an in-situ human skeleton with associated artefacts and ecofacts, displaying rituals of Neolithic burials. The discovery of this skeleton, as well as 41 other human remains recorded previously, indicates that Guar Kepah has been used as the main burial site for Neolithic communities in the area. Furthermore, Guar Kepah is the only site of shell-mound burials in Malaysia to date. Keywords: Guar Kepah, neolithic, burials, human skeletons, shell mound, isotopes